Astaxanthin From Haematococcus pluvialis Prevents High-Fat Diet-Induced Hepatic Steatosis and Oxidative Stress in Mice by Gut-Liver Axis Modulating Properties - Wang, Meng; Xu, Wenxin; Yu, Jie; Liu, Yingying; Ma, Haotian; Ji, Chunli; Zhang, Chunhui; Xue, Jinai; Li, Runzhi; Cui, Hongli (Frontiers in Nutrition, 2022)
Scope: Evidence is mounting that astaxanthin (ATX), a xanthophyll carotenoid, used as a nutritional supplement to prevent chronic metabolic diseases. The present study aims to identify the potential function of ATX supplementation in preventing steatohepatitis and hepatic oxidative stress in diet-induced obese mice. Methods and Results: In this study, ATX as dose of 0.25%, 0.5% and 0.75% have orally administered to mice along with a high-fat diet (HFD) to investigate the role of ATX in regulating liver lipid metabolism and gut microbiota. The study showed that ATX dose-dependently reduces body weight, lipid droplet formation, hepatic triglycerides and ameliorated hepatic steatosis and oxidative stress. 0.75% ATX altered the levels of 34 lipid metabolites related to hepatic cholesterol and fatty acid metabolism which might be associated with downregulation of lipogenesis-related genes and upregulation of bile acid biosynthesis-related genes. The result also revealed that ATX alleviates HFD-induced gut microbiota dysbiosis by significantly inhibiting the growth of obesity-related Parabacteroides and Desulfovibrio while promoting the growth of Allobaculum and Akkermansia. Conclusion: The study results suggested that dietary ATX may prevent the development of hepatic steatosis and oxidative stress with the risk of metabolic disease by gut-liver axis modulating properties.